(untitled) (Global Journal of Human-Social Science, 2011)
This paper is based on primary data collected from the respondent on Women’s encompasses within it. It studies the role of social structural components in developing entrepreneurial orientation among women. Based on an extensive survey of data and empirical findings of two cities in state of Uttarakhand the paper goes on to demonstrate the resistance faced by women entrepreneurs owing to their social habitat and how they managed to overcome the social structural obstacles.